2016
DOI: 10.1186/s12989-016-0179-8
|View full text |Cite
|
Sign up to set email alerts
|

Early kidney damage induced by subchronic exposure to PM2.5 in rats

Abstract: BackgroundParticulate matter exposure is associated with respiratory and cardiovascular system dysfunction. Recently, we demonstrated that fine particles, also named PM2.5, modify the expression of some components of the angiotensin and bradykinin systems, which are involved in lung, cardiac and renal regulation. The endocrine kidney function is associated with the regulation of angiotensin and bradykinin, and it can suffer damage even as a consequence of minor alterations of these systems. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 73 publications
6
48
2
Order By: Relevance
“…Kidney injury molecule-1 (KIM-1) is a type l transmembrane glycoprotein and potential biomarker for the detection of tubular injury in renal diseases [40]. It was reported that the expression of KIM-1 protein in the kidney cortex of the PM 2.5 -exposed group was fourfold higher than those of the control group in SD rats induced by PM 2.5 exposure during the early kidney injury [8]. Our present study showed that exposure to PM 2.5 induced significant increases in the levels of KIM-1 in both a dose-and time-dependent manner, which is indicative of injury to the proximal tubule epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney injury molecule-1 (KIM-1) is a type l transmembrane glycoprotein and potential biomarker for the detection of tubular injury in renal diseases [40]. It was reported that the expression of KIM-1 protein in the kidney cortex of the PM 2.5 -exposed group was fourfold higher than those of the control group in SD rats induced by PM 2.5 exposure during the early kidney injury [8]. Our present study showed that exposure to PM 2.5 induced significant increases in the levels of KIM-1 in both a dose-and time-dependent manner, which is indicative of injury to the proximal tubule epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some epidemiological studies have reported a strong and consistent association between PM 2.5 exposure and reduced kidney function as well as an increased rate of renal function decline [5][6][7]. Studies have also shown that mid-/long-term exposure to high levels of PM 2.5 can induce kidney damage in rodents [8,9]. However, the mechanism of PM 2.5 -induced renal dysfunction remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The strong correlation between chronic kidney disease and cardiovascular disease has been demonstrated by both observational studies and a meta-analysis (Moody et al, 2012). In conditions of renal insu ciency and in patients undergoing dialysis is prone to cardiovascular diseases have been reported in clinical practice, which indicates a potential interaction between the kidney and the cardiovascular system (Aztatzi-Aguilar et al, 2016). Tavera Busso et al observed more severe alterations of brosis, mesangial expansion, tubular epithelial cells detachment, decrease glomerular and tubular lumen volumes in a spontaneously hypertensive rat (SHR) model after sub-chronic exposure to PM 2.5 than healthy animals (Tavera Busso et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Bowe et al estimated that the global burden of incident chronic kidney disease (CKD) attributable to PM 2.5 was about 6.95 million in 2016, and air pollution may be an important risk factor for the prevalence of kidney disease (Bowe et al, 2019). Experimental studies have also shown that mid-/long-term exposure to high levels of PM 2.5 can induce kidney damage in rodent models (Aztatzi-Aguilar et al, 2016;Ge et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a number of epidemiological studies have shown an association between exposure to cadmium and adverse kidney outcomes . With regard to PM2.5, recent experimental and epidemiological studies have provided evidence that PM2.5 exposure is associated with decreased kidney function, and high rate of kidney disease …”
Section: Methodsmentioning
confidence: 99%